2017
DOI: 10.1080/02670844.2016.1259090
|View full text |Cite
|
Sign up to set email alerts
|

Solar photocatalytic activity of nitrogen doped TiO2 coating by micro-arc oxidation

Abstract: Nitrogen doped porous TiO 2 (N-TiO 2 ) coating was developed from titanium nitride (TiN) by micro-arc oxidation (MAO), whereas TiN was prepared by plasma nitriding on commercially pure (Cp) titanium. The surface roughness of the N-TiO 2 coating was greater than that of the TiO 2 coating due to different MAO processing parameters. The band gap energy of N-TiO 2 coating was reduced to 2.92 eV compared to TiO 2 coating. The band gap energy reduction of N-TiO 2 was attributed to nitrogen doping and the mixture of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…where R is the reflectance, and the type of material in this study is considered to have an indirect band gap. 30,31 2.4. Protein Adsorption.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…where R is the reflectance, and the type of material in this study is considered to have an indirect band gap. 30,31 2.4. Protein Adsorption.…”
Section: Methodsmentioning
confidence: 99%
“…The UV–vis DRS were obtained using a UV–vis spectrometer with an integrating sphere (Lambda 750, PerkinElmer Inc., Shelton, CT) ( n = 1). From these spectra, the Tauc plots were obtained via the Kubelka–Munk function, which is given by eq where R is the reflectance, and the type of material in this study is considered to have an indirect band gap. , …”
Section: Experimental Sectionmentioning
confidence: 99%
“…The typical sharp peak at 25° corresponds to the (101) plane of anatase TiO 2 . Apart from the anatase TiO 2 , TiN 0.3 phases are also identified in N-TiO 2 , verifying the doping of N . With regards to the NiFe/N-TiO 2 composite, some additional small peaks show up on the XRD pattern which are indexed to the typical profile of LDH materials. , X-ray photoelectron spectroscopy (XPS) measurements were further performed to testify the elemental composition and chemical valence states of the NiFe/N-TiO 2 .…”
Section: Resultsmentioning
confidence: 93%
“…The XRD results indicated that all the samples contained anatase and rutile, and the main diffraction peaks were sharp. Owing to the porosity and thinness of the coatings, the substrate peaks also emerged along with the two samples, respectively (Sridhar et al , 2016). The anatase was the predominant phase in the coating, and the amount of anatase and rutile phases was calculated based on the following equations (Tanaka and Kaczmarek, 2006): …”
Section: Test Results and Discussionmentioning
confidence: 99%
“…Many efforts have been expanded to propose the absorption of visible light by TiO 2 in the absorption spectrum. Introducing some defects, such as doping nonmetal (Lin et al , 2017; Lee et al , 2015; Cinelli et al , 2017; Sridhar et al , 2016) or metal species (Diaz-Uribe et al , 2014; Belver et al , 2017), in the lattice of titanium dioxide is one of the effective ways to obtain better visible light response. Meanwhile, an effective method, modified TiO 2 by metal ions, proves the expansion of absorption light from ultraviolet to visible region, and reduces the recombination rate of photogenerated electrons and holes (Joung et al , 2006; Wang et al , 2014; Kralova et al , 2014; Zhuang et al , 2015) and coworkers have studied the cerium, silver and iron doped TiO 2 film.…”
Section: Introductionmentioning
confidence: 99%